Solar fed BLDC motor drive for mixer grinder using a boost converter - Deekshitha S Nayak; R Shivarudraswamy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The existing mixer grinder comprises of the universal motor operating in alternating current supply due to high starting torque characteristics and simple controlling of the speed. The absence of brushes and the reduction of noise in the Brushless DC (BLDC) extends its lifetime and makes it ideal in a mixer grinder. A novel solar-powered BLDC motor drive for mixer grinder is presented in this paper. A DC-DC boost converter has been utilised to operate a PV (photovoltaic) array at its highest power. The proposed hysteresis current control BLDC system has been developed in the MATLAB. A performance comparison is made using the commercially available mixer grinder along with the simulated proposed system.